2017
DOI: 10.1111/jgh.13717
|View full text |Cite
|
Sign up to set email alerts
|

Liver damage and senescence increases in patients developing hepatocellular carcinoma

Abstract: Hepatocytes from patients developing HCC go through more pronounced cell damage and senescence in contrast to cirrhotic patients remaining tumor free.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The top 50 significantly up-regulated and down-regulated genes were listed in Figure 2 A. KEGG pathway enrichment analysis of the most significant up-regulated genes showed that the top 5 enriched pathway is cell cycle, cellular senescence, melanoma, p53 signaling pathway, and ECM-receptor interaction. All of these pathways were reported with important roles in cancer 32 - 35 (Figure 2 B). Whereas the top 5 KEGG pathway enriched in the down-regulated genes, including valine, leucine and isoleucine degradation, retinol metabolism, PPAR signaling pathway, fatty acid degradation and complement and coagulation cascades, also have been studied to be important pathways involved in tumor growth and metastasis (Figure 2 B and Table S2 ) 36 - 39 .…”
Section: Resultsmentioning
confidence: 90%
“…The top 50 significantly up-regulated and down-regulated genes were listed in Figure 2 A. KEGG pathway enrichment analysis of the most significant up-regulated genes showed that the top 5 enriched pathway is cell cycle, cellular senescence, melanoma, p53 signaling pathway, and ECM-receptor interaction. All of these pathways were reported with important roles in cancer 32 - 35 (Figure 2 B). Whereas the top 5 KEGG pathway enriched in the down-regulated genes, including valine, leucine and isoleucine degradation, retinol metabolism, PPAR signaling pathway, fatty acid degradation and complement and coagulation cascades, also have been studied to be important pathways involved in tumor growth and metastasis (Figure 2 B and Table S2 ) 36 - 39 .…”
Section: Resultsmentioning
confidence: 90%
“…It is possible that disruption of this process might allow for reduced viral replication and immune clearance of an often chronic and damaging infection. In addition, studies have demonstrated higher levels of cellular senescence at the hepatocyte level leading to an increased risk of HCC, with this being compounded by the impaired clearance of said senescent hepatocytes by immune cells 31,32. These findings demonstrate the complex interplay between hepatic and immune telomerase maintenance while highlighting the telomerase complex as a possible therapeutic target 29…”
Section: Discussionmentioning
confidence: 96%
“…Taking into consideration the confidence on 8-oxodG determination as a good marker of DNA damage, our findings are remarkable indicating a broad damage induced by DEN in an hypercholesterolemic environment. Even more, activation of the H2AX, another excellent marker for DNA damage in humans [ 31 ], confirms the exacerbation of the genomic damage promoted by the high cholesterol liver content and DEN treatment.…”
Section: Discussionmentioning
confidence: 99%